2015
DOI: 10.2147/ceg.s91964
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal motility during sleep assessed by tracking of telemetric capsules combined with polysomnography – a pilot study

Abstract: Studies of gastrointestinal function during sleep are hampered by lack of applicable techniques. Recent development of a novel ambulatory telemetric capsule system, which can be used in conjunction with polysomnography, offers a solution to this problem. The 3D-Transit system consists of ingestible electromagnetic capsules traceable through a portable extracorporeal receiver while traversing the gut. During sleep monitored by polysomnography, gastrointestinal motility was concurrently investigated using 3D-Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…The present study focuses solely on colonic recordings. Ileocecal passage was determined by the capsule's two‐dimensional location in the lower right abdomen and a decrease in contraction frequency from six to three contractions per minute . Prior to classification of movement patterns, all fast capsule movements (>4 cm with a mean velocity >4 cm/min) were identified using an automated algorithm (Motilis Medica SA) .…”
Section: Methodsmentioning
confidence: 99%
“…The present study focuses solely on colonic recordings. Ileocecal passage was determined by the capsule's two‐dimensional location in the lower right abdomen and a decrease in contraction frequency from six to three contractions per minute . Prior to classification of movement patterns, all fast capsule movements (>4 cm with a mean velocity >4 cm/min) were identified using an automated algorithm (Motilis Medica SA) .…”
Section: Methodsmentioning
confidence: 99%
“…Colorectal lengths were estimated using the 3D-Transit position data from the electromagnetic pill recordings. Ileocaecal passage of the capsule was located using the same method as described in previous publications [10][11][12][13][14]. Data recorded from ileocaecal passage to expulsion were regarded as recordings from the colorectum.…”
Section: Total and Segmental Colorectal Lengths Assessed With 3d-transitmentioning
confidence: 99%
“…It is known that there is a profound inhibitory effect on gastrointestinal (GI) motility pattern during sleep. Several studies have demonstrated the suppression of both gastric and colonic motilities . On the other hand, the delay in gastric emptying due to the supine position is controversial.…”
Section: Influence Of Meal Intake On Gastric Physiologymentioning
confidence: 99%
“…Several studies have demonstrated the suppression of both gastric and colonic motilities. [46][47][48][49] On the other hand, the delay in gastric emptying due to the supine position is controversial. Some studies have shown no significant effect of body position in the gastric emptying time, [50][51][52] whereas others have shown differences in GET due to changes in body position.…”
Section: Influence Of Meal Intake On Gastric Physiologymentioning
confidence: 99%